Local recovery of cardiac calcium‐induced calcium release interrogated by ultra‐effective, two‐photon uncaging of calcium. (2nd August 2021) - Janicek, Radoslav; Agarwal, Hitesh; Gómez, Ana M.; Egger, Marcel; Ellis‐Davies, Graham C. R.; Niggli, Ernst
Abstract : Key points: In cardiac myocytes, subcellular local calcium release signals, calcium sparks, are recruited to form each cellular calcium transient and activate the contractile machinery. Abnormal timing of recovery of sparks after their termination may contribute to arrhythmias. We developed a method to interrogate recovery of calcium spark trigger probabilities and their amplitude over time using two‐photon photolysis of a new ultra‐effective caged calcium compound. The findings confirm the utility of the technique to define an elevated sensitivity of the calcium release mechanism in situ and to follow hastened recovery of spark trigger probabilities in a mouse model of an inherited cardiac arrhythmia, which was used for validation. Analogous methods are likely to be applicable to investigate other microscopic subcellular signalling systems in a variety of cell types. Abstract: In cardiac myocytes Ca 2+ ‐induced Ca 2+ release (CICR) from the sarcoplasmic reticulum (SR) through ryanodine receptors (RyRs) governs activation of contraction. Ca 2+ release occurs via subcellular Ca 2+ signalling events, Ca 2+ sparks. Local recovery of Ca 2+ release depends on both SR refilling and restoration of Ca 2+ sensitivity of the RyRs. We used two‐photon (2P) photolysis of the ultra‐effective caged Ca 2+ compound BIST‐2EGTA and laser‐scanning confocal Ca 2+ imaging to probe refractoriness of local Ca 2+ release in control conditions and in the presence of cAMP or low‐dose caffeine (to stimulate CICR) or cyclopiazonic acid (CPA; to slow SR refilling). Permeabilized cardiomyocytes were loaded with BIST‐2EGTA and rhod‐2. Pairs of short 2P photolytic pulses (1 ms, 810 nm) were applied with different intervals to test Ca 2+ release amplitude recovery and trigger probability for the second spark in a pair. Photolytic and biological events were distinguished by classification with a self‐learning support vector machine (SVM) algorithm. In permeabilized myocytes data recorded in the presence of CPA showed a lower probability of triggering a second spark compared to control or cAMP conditions. Cardiomyocytes from a mouse model harbouring the arrhythmogenic RyR R420Q mutation were used for further validation and revealed a higher Ca 2+ sensitivity of CICR. This new 2P approach provides composite information of Ca 2+ release amplitude and trigger probability recovery reflecting both SR refilling and restoration of CICR and RyR Ca 2+ sensitivity. It can be used to measure the kinetics of local CICR recovery, alterations of which may be related to premature heart beats and arrhythmias. Key points: In cardiac myocytes, subcellular local calcium release signals, calcium sparks, are recruited to form each cellular calcium transient and activate the contractile machinery. Abnormal timing of recovery of sparks after their termination may contribute to arrhythmias. We developed a method to interrogate recovery of calcium spark trigger probabilities and their amplitude over time using two‐photon photolysis of a new ultra‐effective caged calcium compound. The findings confirm the utility of the technique to define an elevated sensitivity of the calcium release mechanism in situ and to follow hastened recovery of spark trigger probabilities in a mouse model of an inherited cardiac arrhythmia, which was used for validation. Analogous methods are likely to be applicable to investigate other microscopic subcellular signalling systems in a variety of cell types.